The readiness of agricultural industry to venture into the international market (A case study on Pela Agro Management and Services) / Siti Syukriah Seff Ahmad - Seff Ahmad, Siti Syukriah (2010)
The purpose of this study is to identify the readiness of agricultural industry to venture into international market based on the factors of management, marketing, financial resource, human resources and production. This study focuses on Pela Agrotech Management and Services which is one of the Terengganu agricultural companies. TADC also play an important role where it helps the company in marketing process. The company is in the mature stages where the demand for company products is high especially from supermarket, hotel and airplane companies such as AirAsia and Malaysia Airport. Therefore, they will venture into international market in order to reduce the bumping phenomenon in local market. The desire to export does not equal to an ability to or capacity to export. So, export ready assumes that key aspect of company have met a certain threshold which means the company has the resource to initiate and capacity to sustain an export activity, and the important thing is having product demand in foreign market that has some level of competitive or comparative advantages. After interview and observe the company, the company is ready for the overall perspective such as management, marketing, financial, human resource and the productions. Besides, with the assistance of Terengganu Development Corporation Sdn Bhd (TADC) which is one of the government agencies, the company has the potential and ability to venture into international market. From analysis and findings, recommendation is cover the business plan, research and development for the product quality and the strategy that the company can apply in order to maintain their products in abroad market for the future.